Cost-effectiveness analysis of implementing polygenic risk score in a workplace cardiovascular disease prevention program - Mujwara, Deo; Kintzle, Jen; Di Domenico, Paolo; Busby, George B.; Bottà, Giordano (Frontiers in Public Health, 2023)
Implementing a polygenic risk score for coronary artery disease (CAD-PRS) as an additional risk enhancing factor in the current cardiovascular risk assessment models improves precision in assessing the risk of cardiovascular diseases and is cost-effective in a health system. Workplaces provide a conducive environment for cardiovascular prevention interventions but the cost-effectiveness of CAD-PRS in a workplace setting remains unknown. This study examined the cost-effectiveness of integrating CAD-PRS in a workplace cardiovascular disease prevention program compared to the standard cardiovascular workplace program without CAD-PRS and no-workplace prevention program. We developed a cohort simulation model to project health benefits (quality-adjusted life-years gained) and costs over a period of 5 years in a cohort of employees with a mean age of 50 years. The model health states reflected risk of disease (coronary artery disease and ischemic stroke) and statin prevention therapy side-effects (diabetes, hemorrhagic stroke and myopathy). We considered medical and lost productivity costs. Data came from the literature and the analysis was performed from a self-insured employer perspective with future costs and quality-adjusted life-years discounted at 3% annually. Uncertainty in model parameter inputs was assessed using deterministic and probabilistic sensitivity analyses. Three programs were compared: 1) a workplace cardiovascular program that integrated PRS with the pooled cohort equation—standard of care for assessing the risk of cardiovascular diseases—(CardioriskSCORE); 2) a workplace cardiovascular prevention program without PRS (No-PRS); 3) no workplace health program (No-WHP). Main outcomes were total costs (2019 US ), incremental costs, incremental quality-adjusted life-years, and incremental cost-effectiveness ratio. CardioriskSCORE lowered employer costs (53 and 575) and improved employee quality-adjusted of life years (0.001 and 0.005) per employee screened compared to No-PRS and No-WHP, respectively. Effectiveness of statin prevention therapy, employee’s baseline cardiovascular risk, proportion of employees that enrolled in the program and statin adherence had the largest effect size on the incremental net monetary benefit. However, despite the variation in parameter input values, base case results remained robust. Polygenic testing in a workplace cardiovascular prevention program improves employee quality of life and simultaneously lowers health costs and productivity monetary loss for employers.